1998
DOI: 10.2172/671989
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication of polysilicon micromechanisms with self-assembled monolayers

Abstract: Here, we report on the lubricating effects of self-assembled monolayers (SAMs) on MEMS by measuring static and dynamic friction with two polysilicon surface-micromachined devices. The first test structure is used to study friction between laterally sliding surfaces and with the second, friction between vertical sidewalls can be investigated. Both devices are SAM-coated following the sacrificial oxide etch and the microstructures emerge released and dry from the final water rinse. The coefficient of static fric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…For rubbing surfaces, both Senft [82] and Srinivasan et al [83] have observed lowered coefilcient of friction for SAM coated devices. The wear properties are still under investigation.…”
Section: Lubricationmentioning
confidence: 96%
See 2 more Smart Citations
“…For rubbing surfaces, both Senft [82] and Srinivasan et al [83] have observed lowered coefilcient of friction for SAM coated devices. The wear properties are still under investigation.…”
Section: Lubricationmentioning
confidence: 96%
“…Early work by Gabriel [56] using air-dried turbines measured the dynamic COF between polysilicon and silicon near 0.3. Work by Srinivasan et al [68] suggests that nanometer thick surface treatments can act as a boundary lubricant and reduce the dynamic COF between FTS-coated polysilicon surfaces to 0.08. The normal force in Srinivasan's experiments was roughly 5~and total number of cycles was in the 105 to 106 range, which is applicable to what the microengines experience.…”
Section: Scc02 Vs Ftsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FOTAS molecule design includes a tri-amino head group to promote covalent bonding to the silanol surface via a nucleophilic reaction, and a perfluorinated tail group to minimize surface energy. The FOTAS molecule was developed as a replacement for solvent-deposited CF 3 (CF 2 ) 7 (CH 2 ) 2 SiCl 3 , (FDTS) [22] for two reasons. First, the vapor-phase deposition is more reproducible because FDTS is prone to form micelles and multilayers during the liquid solvent deposition [23].…”
Section: Device and Test Proceduresmentioning
confidence: 99%
“…The PFOTS monolayer shows high values of coefficient of friction, indicating that the effect of size of fluorine atom influences the friction behaviour even at the micro-scale [15,20,21,26]. Other researchers too have observed high values of friction in the similar class of fluorinated SAM (perfluorodecyltrichlorosilane, FDTS) [27][28][29]. The PFDA monolayer shows high values of friction followed by wear.…”
Section: Friction At Nano-scalementioning
confidence: 99%